2020
DOI: 10.3390/joitmc6040101
|View full text |Cite
|
Sign up to set email alerts
|

Does Open Innovation Enhance a Large Firm’s Financial Sustainability? A Case of the Korean Food Industry

Abstract: This study aims to explore whether a firm’s financial sustainability is enhanced by open innovation especially after a global financial crisis. There are few studies on the relationship between open innovation and financial sustainability. This study aimed to fill the literature gap by analyzing the change in the financial ratio according to the increase or decrease in open innovation. We used a case study method regarding large Korean food firms. Korea is a latecomer in the food industry, which is driven by l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 60 publications
0
29
0
1
Order By: Relevance
“…Socioeconomic changes such as price hikes and hunger problems follow. Each actor in the value chain needs to promote sustainable growth by increasing productivity and profitability in a stable financial environment [29].…”
Section: Value Chain In Food Industrymentioning
confidence: 99%
“…Socioeconomic changes such as price hikes and hunger problems follow. Each actor in the value chain needs to promote sustainable growth by increasing productivity and profitability in a stable financial environment [29].…”
Section: Value Chain In Food Industrymentioning
confidence: 99%
“…Many research findings show that the level of absorptive capacity has a significant influence on a firm's innovation activities and performance [16,[34][35][36][37][38]. Studies on Western firms have suggested that absorptive capacity positively influences a firm's innovation performance, including new product development [17,33,36].…”
Section: Absorptive Capacitymentioning
confidence: 99%
“…Studies on Western firms have suggested that absorptive capacity positively influences a firm's innovation performance, including new product development [17,33,36]. In addition, some studies on Korean firms have suggested that absorptive capacity increases patent registrations and improves financial performance [2,24,34,37,38]. Other studies have reported that firms' performance may decline when their absorptive capacity rises above a certain level in technical cooperation with a partner firm [39].…”
Section: Absorptive Capacitymentioning
confidence: 99%
See 2 more Smart Citations